2022
DOI: 10.1021/acsapm.2c00097
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Shear Stiffening in Polymer-Grafted Nanoparticle Composites for High-Temperature Adhesives

Abstract: Thermally activated shear stiffening viscoelastic fluid can help to improve the performance of viscoelastic dampers and high-temperature adhesives. Polymer nanocomposites with heterogeneous interphases are applied to design such adaptive materials. In this work, shear stiffening in polymer-grafted nanoparticle composites is investigated. We report the linear rheological responses of grafted particle composites before and after large-amplitude oscillatory shear application. We found that interfacial mixing of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…It is worth mentioning that rheological properties of the grafted composites were tested and reported in our previous work. 41 We found that short matrix chains dynamically coupled better with the long-grafted chains and reinforced the system at high temperatures. Here, we will present the relaxations of PMMA-grafted Fe 3 O 4 (15 nm) nanoparticles in 20 kDa and 160 kDa PMA matrices.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…It is worth mentioning that rheological properties of the grafted composites were tested and reported in our previous work. 41 We found that short matrix chains dynamically coupled better with the long-grafted chains and reinforced the system at high temperatures. Here, we will present the relaxations of PMMA-grafted Fe 3 O 4 (15 nm) nanoparticles in 20 kDa and 160 kDa PMA matrices.…”
Section: Resultsmentioning
confidence: 76%
“…This dense layer effect was verified by the higher reinforcement observed with the short (20 kDa) PMA chains in our previous work. 41…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermally activated shear stiffening for the grafted chain in a polymer matrix was observed by Wu et al (2022). The thermal stiffening effect can be used in devices that require high modulus and high viscosity under the oscillating shear application.…”
Section: Discussion: Tuning Of Mechanical Propertiesmentioning
confidence: 99%